1972
DOI: 10.2172/4569664
|View full text |Cite
|
Sign up to set email alerts
|

Ductile-brittle behavior of Zircaloy fuel cladding.

Abstract: This paper describes the results of two sets of experiments designed to characterize the ductile-brittle behavior of Zircaloy fuel element cladding in terms of amount of oxidation, degree of penetration of brittle phases into the tube wall, and type of deformation used in the tests.Ring specimens were cut from 0.422-in. OD x 0.027-in.-wall thickness Zircaloy-4 tubes previously steam-oxidized on both inner and outer surfaces at temperatures ranging from 1700 to 2400°F for various times. Two typas of deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They reported that the correlation obtained below 1,477 K is invalid and the cladding embrittlement cannot be predicted only by the unoxidized metallic layer thickness for the higher temperature range. 14,15) This result became the basis for the temperature limit (1,473 K (1,200 C)) in the ECCS acceptance criteria. Concerning this observation, Hobson suggested that not only the metallic thickness but also the amount or distribution of oxygen in the metallic layer should be taken into account.…”
Section: Fracture Conditionsmentioning
confidence: 89%
“…They reported that the correlation obtained below 1,477 K is invalid and the cladding embrittlement cannot be predicted only by the unoxidized metallic layer thickness for the higher temperature range. 14,15) This result became the basis for the temperature limit (1,473 K (1,200 C)) in the ECCS acceptance criteria. Concerning this observation, Hobson suggested that not only the metallic thickness but also the amount or distribution of oxygen in the metallic layer should be taken into account.…”
Section: Fracture Conditionsmentioning
confidence: 89%
“…Hobson [16] and Hobson and Rittenhouse [17] performed low-and high-strain-rate ring compression tests, respectively, using two-sided oxidized Zry-4 cladding samples over a wide range of temperatures. The results of the low-strain-rate tests interpolated to ≈135ºC (275ºF) were used to formulate the 1204ºC (2200ºF) peak cladding temperature and 17% maximum oxidation level (Baker-Just ECR [12]).…”
Section: Ductility Determination Using Ring-compression Testsmentioning
confidence: 99%
“…The second step is to select the most appropriate parameter characterising the oxidation and hydriding amount on which to correlate embrittlement, so as to find out an alternative to the ECR. It is based on the previous work from early investigators ( [6][7][8][9], etc.). At that time, research programs and calculation tools were not ready to make successful these attempts.…”
Section: Cladding Embrittlementmentioning
confidence: 99%